Giambattista Della Porta, Dramatist - Clubb, Louise George (Book collections on Project MUSE., 1965)
Although Renaissance scholars generally agree that Della Porta was the finest comic playwright of his generation in Italy, no detailed analysis of these plays and of their considerable influence outside Italy has previously appeared. One of the most famous men of his time in the field of scientific investigation, Della Porta wrote plays for relaxation and, on occasion, to camouflage controversial aspects of his scientific research from the Inquisitions. Today his works in science are largely forgotten and his right to fame rests on the plays. This book brings together the available facts of Della Porta's rich and often mysterious life and closely examines his dramatic works as part of the Italian literary scene in late Renaissance. Originally published in 1965. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.